2011
DOI: 10.1089/ham.2011.0008
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and Frostbite on Mount Everest: New Insights into Wind Chill and Freezing Times at Extreme Altitude

Abstract: Cold injury is an acknowledged risk factor for those who venture into high altitude regions. There is, however, little quantitative information on this risk that can be used to implement mitigation strategies. Here we provide the first characterization of the risk of cold injury near the summit of Mount Everest. This is accomplished through the application of a meteorological dataset that has been demonstrated to characterize conditions in the region as inputs to new parameterizations of wind chill equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 21 publications
11
48
0
Order By: Relevance
“…During the spring climbing season, WCTs of −50°C and FFTs of 5 min are typical; while during severe storms, they can approach −60°C and 1 min, respectively. During the May 1996 ‘Into Thin Air’ storm, the instantaneous WCT and FFT approached values typically found during the winter months [17]. This work highlighted the crucial role that wind speed played in increasing the hypothermic stress near the summit and also confirmed that the previous estimate was biased low as a result of the assumption as to the magnitude of the wind speed in the region [16].…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…During the spring climbing season, WCTs of −50°C and FFTs of 5 min are typical; while during severe storms, they can approach −60°C and 1 min, respectively. During the May 1996 ‘Into Thin Air’ storm, the instantaneous WCT and FFT approached values typically found during the winter months [17]. This work highlighted the crucial role that wind speed played in increasing the hypothermic stress near the summit and also confirmed that the previous estimate was biased low as a result of the assumption as to the magnitude of the wind speed in the region [16].…”
Section: Introductionsupporting
confidence: 73%
“…In addition, it must be emphasized that these expressions were derived at sea level and there are meteorological and physiological issues with applying them at altitude [16,17]. In particular, the convective heat loss is proportional to the square root of the Reynolds number, which in turn depends on the product of the air density and wind speed [25].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations